2005
DOI: 10.1097/01.mlg.0000181461.63392.49
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Bionics Thin Lateral and Helix II Electrodes: A Temporal Bone Study

Abstract: Both electrodes performed favorably in our human temporal bone trials, and both arrays appear promising for clinical use, especially in patients with residual hearing in whom atraumatic insertion is an important objective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…When fully inserted in temporal bones the HiFocus 1J electrode was positioned with a mean distance of 1.23 mm (electrode n=4) from the modiolus [120]. Although there have been no quantitative studies of the Combi array published to date it is reasonable to assume that the position of this electrode would be similar and published images of this electrode in place confirm their location near the spiral ligament.…”
Section: ) Standard Arrays-the Advanced Bionics Hifocus Helix™ and mentioning
confidence: 94%
See 3 more Smart Citations
“…When fully inserted in temporal bones the HiFocus 1J electrode was positioned with a mean distance of 1.23 mm (electrode n=4) from the modiolus [120]. Although there have been no quantitative studies of the Combi array published to date it is reasonable to assume that the position of this electrode would be similar and published images of this electrode in place confirm their location near the spiral ligament.…”
Section: ) Standard Arrays-the Advanced Bionics Hifocus Helix™ and mentioning
confidence: 94%
“…To access lower frequency components of the speech spectra (200-1200 Hz), it is necessary to insert the electrode array to an approximate depth of 1.5 cochlear turns or 540° degrees measured from the round window. Recent studies have shown that in most cases the current generation of electrodes can be inserted to a depth of less than 400° and that deeper insertion results in higher rates of intracochlear damage and misplaced electrodes [119,120 ]. Thus, significant advances in electrode design will be required to reliably achieve optimum insertion depth with minimal trauma.…”
Section: A Design Goals For Intracochlear Electrodesmentioning
confidence: 99%
See 2 more Smart Citations
“…Wright [25] embedded the specimens in a medium, subjected to EDTA decalcification, before drilling the upper portion of the osseous labyrinth to visualize the electrode array across the osseous spiral lamina and basilar membrane to evaluate their integrity. Adunka [1] embedded the implanted cochleae in polymethacrylate subsequent to infusion with physiological serum via the oval window and took sequential sections spaced 100 microns apart.…”
Section: Discussionmentioning
confidence: 99%